2016
DOI: 10.1111/cdoe.12211
|View full text |Cite
|
Sign up to set email alerts
|

Adverse birth outcomes and childhood caries: a cohort study

Abstract: Objectives To examine the association between adverse birth outcomes and dental caries in primary teeth. Methods This study included children in Khon Kaen, Thailand, who participated in the Prospective Cohort Study of Thai Children. Preterm was defined as a birth at <37 weeks gestation, low birthweight (LBW) as birthweight <2,500 grams, and small-for-gestational-age (SGA) as birthweight <10th percentile of expected weight for gestational age. Two calibrated dentists measured dental caries in primary teeth wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 32 publications
3
59
0
1
Order By: Relevance
“…To the best of our knowledge, there were no other studies observing caries prevalence and experience within the birth weight categories ELBW, VLBW, and LBW. In the literature, LBW was not associated with dental caries in the primary dentition [Shulman, 2005;Tanaka and Miyake, 2014;Nirunsittirat et al, 2016]. The association between LBW and DDE found in other studies [Lunardelli and Peres, 2006;Ferrini et al, 2008;Velló et al, 2010;Takaoka et al, 2011;Cruvinel et al, 2012;Masumo et al, 2013;Nelson et al, 2013;Elfrink et al, 2014] was confirmed by the present data.…”
Section: Risk Factorssupporting
confidence: 89%
See 2 more Smart Citations
“…To the best of our knowledge, there were no other studies observing caries prevalence and experience within the birth weight categories ELBW, VLBW, and LBW. In the literature, LBW was not associated with dental caries in the primary dentition [Shulman, 2005;Tanaka and Miyake, 2014;Nirunsittirat et al, 2016]. The association between LBW and DDE found in other studies [Lunardelli and Peres, 2006;Ferrini et al, 2008;Velló et al, 2010;Takaoka et al, 2011;Cruvinel et al, 2012;Masumo et al, 2013;Nelson et al, 2013;Elfrink et al, 2014] was confirmed by the present data.…”
Section: Risk Factorssupporting
confidence: 89%
“…The differences were significant for the occurrence of cavitated and noncavitated caries lesions (ICDAS II criteria) and for caries experience (DMFT criteria). Few studies reported a higher caries prevalence in PTI [Saraiva et al, 2007;Carvalho et al, 2011], while others found nonsignificant lower caries prevalence in PTI compared to FTI [Burt and Pai, 2001;Cruvinel et al, 2010;Nelson et al, 2010;Rythen, 2012;Tanaka and Miyake, 2014;Nirunsittirat et al, 2016;Wagner and Heinrich-Weltzien, 2016]. Factors that may contribute to a higher risk of dental caries in PTI could be the impaired immune response leading to earlier colonization by cariogenic bacteria and the association of prematurity and LBW with deprived SES of the mother [Burt and Pai, 2001;Shulman, 2005].…”
Section: Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to congratulate Community Dentistry and Oral Epidemiology for the publication of the article 'Adverse birth outcomes and childhood caries: a cohort study' by Nirunsittirat et al 1 Indeed, it is vital to improve the understanding of early child's oral health determinants and consequent identification of interventions and behaviors that can be modified with health promotion activities since birth. Authors have suggested that proper fetal growth and adequate development in the first two years of life are determinants of health, not only at childhood but also in later life 2,3 .…”
Section: Dear Editormentioning
confidence: 99%
“…У зв'язку з широким поширенням хвороб тканин пародонта і твердих тканин зубів особлива увага вчених привертається до питань формування цих тканин. Віддалені наслідки перинатальної патології, зокрема вплив вагітності, яка патологічно протікає, на формування стоматологічних порушень на сьогоднішній день є парадигмою [1,2,3].…”
unclassified